Laws Regarding Family Inclusive of Marriage, Dowry, Custody, Divorce, Maintenanace and Inheritance - Dr. Syed Hasnat Ahmad Shah Gillani; Dr. Noor-Ul- Ain Shabbir; Asmara Farzand (AL-IDRAK JOURNAL, 2024)
Family law is a branch of law that governs the relationships and obligations between individuals within a family, covering areas such as marriage, dowry, custody, divorce, maintenance, and inheritance. These laws serve to protect individuals, ensure justice, and provide solutions to various familial conflicts. The importance of family law cannot be overstated, as it establishes the legal framework that defines rights and responsibilities in a family structure. It not only ensures the protection of rights but also aims to resolve disputes and guide individuals through the complexities of family life. The laws vary from country to country, influenced by cultural practices, religious beliefs, and social norms. Marriage is the legal union between two individuals, recognized by law, which establishes certain rights and responsibilities. This paper aims to present that certain social practices are not condition for marriage, and laws prohibit these practices such as dowery etc. similarly it discusses Custody laws that primarily focus on the protection and welfare of children in cases of marital separation or divorce. When parents separate or divorce, the court determines which parent will have physical and legal custody of the children. Along the side it also discusses that Divorce is the legal dissolution of a marriage, and family laws provide the procedures and grounds for divorce. The aim of divorce laws is to ensure that both parties are treated fairly and that any dependents, especially children, are not adversely affected by the dissolution of the marriage.it also touches the issue of maintenance and Inheritance laws that refers to the financial support provided by one spouse to the other after divorce or separation, or by parents to children for their upkeep and inheritance laws determine how a deceased person’s estate is distributed among heirs, ensuring that family members receive their rightful share of assets according to the order of succession.